Investigation Of Predictable And Numerical Pulse Width Modulation Control Scheme For BLDC Motor Drive System - et. al., K. Bhaskar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper shows check the traditional, CPWM (computerized pulse width modulation) regulator combine for control of speed by the automatic group the Brushless dc (BLDC) motor, from these strategies, pursue from CPWM speed control system, the main distinction is in the regulator part. Unique drive framework comprises of a steady Proportional Integrator controller and different has an advanced controller. This paper remembers conversation for the execution of both the strategies and their exhibitions are thought about.